To solve the quadratic equation \( x^2 - 6x - 16 = 0 \) using the quadratic formula, we start with the general form of a quadratic equation:
\[ ax^2 + bx + c = 0 \]
In this case, \( a = 1 \), \( b = -6 \), and \( c = -16 \).
The quadratic formula is given by:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
- Calculate the discriminant \( b^2 - 4ac \):
\[ b^2 = (-6)^2 = 36 \] \[ 4ac = 4 \cdot 1 \cdot (-16) = -64 \] \[ b^2 - 4ac = 36 - (-64) = 36 + 64 = 100 \]
- Now, substitute \( b \) and the discriminant into the quadratic formula:
\[ x = \frac{-(-6) \pm \sqrt{100}}{2 \cdot 1} = \frac{6 \pm 10}{2} \]
- Calculate the two possible values for \( x \):
First solution:
\[ x = \frac{6 + 10}{2} = \frac{16}{2} = 8 \]
Second solution:
\[ x = \frac{6 - 10}{2} = \frac{-4}{2} = -2 \]
Thus, the solutions to the equation \( x^2 - 6x - 16 = 0 \) are:
\[ x = 8 \quad \text{and} \quad x = -2 \]
The correct response is:
\( x = 8, x = -2 \)
or
\( x \text{ equals } 8, x \text{ equals } -2 \)